DOZ047.18: Diagnosing reflux aspiration in esophageal atresia: role of microbiome and pepsin. (24th June 2019) - Krishnan, U; Singh, H; Kaakoush, N; Leach, S
Abstract: Background: Children with esophageal atresia (EA) often suffer from gastroesophageal reflux disease (GERD) and it's complications, including reflux aspiration. Reflux aspiration can be difficult to diagnose in these patients who often have other causes for their respiratory symptoms. Tracheal pepsin has been studied as a marker of reflux aspiration in other conditions but not in EA. The role of the airway microbiome in the diagnosis of reflux aspiration has not been studied previously. Aims: The aim of this study was to examine the composition of the airway (tracheal aspirate) microbiome of EA patients and correlate the results of the microbial analysis with the presence of gastric pepsin in the airways as a marker of reflux aspiration. Methods: A cohort of children with EA was prospectively recruited at Sydney Children's Hospital in 2018. The EA group were subdivided into children with GERD, eosinophilic esophagitis (EoE), and those with no disease. Tracheal aspirates were collected. The bacterial component (16S rRNA gene) of the microbiome was amplified. Pepsin was assayed using a monoclonal antibody specific for pepsin A by the ELISA technique. Results: There were 26 EA patients. The mean age was 6.96 years (0.7–18) and 15 (58%) were female. Eighteen (69%) children were on proton pump inhibitors for GERD and 8 (30%) were on swallowed steroids for EoE. GERD, defined as reflux esophagitis on biopsy and/or abnormal result on pH/impedance testing, was present in 7 (27%) and EoE defined as >15 eosinophils/HPF was seen in 5 (19%) children. Tracheal pepsin was detected in a significant proportion of EA patients and correlation between the pepsin results and the airway microbial analysis was seen in some of the EA patients who were pepsin positive. Conclusions: This study is the first to examine the role of the microbiome and pepsin in tracheal aspirates as markers of reflux aspiration in children with EA. These results require validation in larger cohorts.